Effect of Extracellular Matrix Membrane on Bone Formation in a Rabbit Tibial Defect Model. (7th March 2016) - Hwang, Jin Wook; Kim, Sungtae; Kim, Se Won; Lee, Jong Ho
Abstract : Absorbable extracellular matrix (ECM) membrane has recently been used as a barrier membrane (BM) in guided tissue regeneration (GTR) and guided bone regeneration (GBR). Absorbable BMs are mostly based on collagen, which is more biocompatible than synthetic materials. However, implanted absorbable BMs can be rapidly degraded by enzymes in vivo . In a previous study, to delay degradation time, collagen fibers were treated with cross-linking agents. These compounds prevented the enzymatic degradation of BMs. However, cross-linked BMs can exhibit delayed tissue integration. In addition, the remaining cross-linker could induce inflammation. Here, we attempted to overcome these problems using a natural ECM membrane. The membrane consisted of freshly harvested porcine pericardium that was stripped from cells and immunoreagents by a cleaning process. Acellular porcine pericardium (APP) showed a bilayer structure with a smooth upper surface and a significantly coarser bottom layer. APP is an ECM with a thin layer (0.18–0.35 mm) but with excellent mechanical properties. Tensile strength of APP was 14 . 15 ± 2.24  MPa. In in vivo experiments, APP was transplanted into rabbit tibia. The biocompatible material was retained for up to 3 months without the need for cross-linking. Therefore, we conclude that APP could support osteogenesis as a BM for up to 3 months.